PENGEMBANGAN INSTRUMEN SIKAP TERHADAP STATISTIKA PADA MAHASISWA CALON GURU MATEMATIKA - Naqiyah, Amniatin; Hayati, Laila; Kertiyani, Ni Made Intan; Arjudin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to produce an attitude instrument towards statistics developed from the Attitude Toward Statistics Survey-36 (SATS-36) and check its level of validity and reliability. This research is development research using 4D models developed by Thiagarajan. Analysis of the validity of the translation is included in the valid category. Meanwhile, content validity is measured by looking at aspects of substance, language, construction and practicality. The results of the instrument's content validity show that the instrument is suitable for use. The trial was carried out on 250 students of the Mathematics Education study program to determine the construct validity and reliability of the instrument. The instrument formed consists of 5 factors with factor loading values ​​for all items > 0.35. The reliability of the instrument developed was 0.762, including the good category. The instrument developed has evidence of validity and reliability, so the instrument is suitable for use to measure student attitudes towards statistics.